Child maltreatment and mental disorders: the role of epigenetics - Queirós,Marta (2018)
Introduction: Child maltreatment is associated with high risk for various physical and mental disorders and is associated with over 30% of adult psychopathology. Child maltreatment also relates with poor clinical outcomes, such as chronic disease, increased hospitalization, comorbidity and reduced response to treatment. Early adverse experiences can cause epigenetic changes, altering gene expression without changing DNA sequence. Epigenetic alterations in genes implicated in stress response and neurodevelopment might explain to some extent the impact of child maltreatment in mental health. Objectives: Review available literature concerning the impact of child maltreatment in human epigenome, focusing on mental health related outcomes. Development: DNA methylation induced by child maltreatment changes specific genes, in peripheral and brain tissues, producing major consequences in stress regulation, neural plasticity, and neurodevelopment. Methylation of the glucocorticoid receptor gene is one of the most studied epigenetic alterations that have been related to childhood maltreatment and seems to be responsible for an increased vulnerability to develop psychopathology. Epigenetic changes may not be permanent, and there are some interventions that seem to reduce DNA methylation. Therefore, in the future, DNA methylation may be used, not only in the diagnosis and prediction of treatment response, but also for therapeutic innovation. Conclusions: Epigenetic changes can potentially explain pathophysiological changes related to child maltreatment exposure, may serve as biomarkers in stress-related disorders and provide targets for the development of new therapeutic and preventive interventions for individuals that were exposed to child abuse.